Preoperative Pulmonary Function test and Pulse Oximetry among Patients Recovered from COVID-19 Who Were Candidates for Elective Surgery - Massoudi, Nilofar; Nasiri, Mohammad Javad; Nooraei, Navid; Abniki, Malihe (Novelty in Biomedicine, 2024)
Background: This descriptive study aimed to assess preoperative pulmonary function test (PFT) results and pulse oximetry readings in patients recovered from COVID-19 who were candidates for elective surgery. Materials and Methods: This is a descriptive study. A total of 110 patients (men = 51) with a mean age of 52.6 years were enrolled in the study. The study protocol was presented to the ethics committee and received approval. Participants included patients with a positive SARS-CoV-2 PCR test history, with a recovery period of at least 6-8 weeks for symptomatic patients and four weeks for asymptomatic patients. Data collection involved a random selection, obtaining informed consent, and conducting a history and physical examination. Pulmonary function capacity and oxygen saturation were assessed, and frailty was evaluated using the Edmonton Frail Scale. Echocardiography and electrocardiography were performed on all patients. Results: The study participants mainly underwent trans-ureteral lithotripsy (TUL), laparoscopic cholecystectomy (LC), and percutaneous nephrolithotomy (PCNL). Symptomatic patients exhibited lower pulse oximetry readings than asymptomatic patients (91.18% vs. 96.13%, p-value = 0.005). Although the average ejection fraction was slightly lower in symptomatic patients (44.25%) compared to asymptomatic patients (48.18%), the difference was insignificant. Symptomatic patients also had higher rates of abnormalities in chest X-rays, electrocardiograms, pulmonary function tests, and fasting blood sugar levels, as well as a higher rate of ICU admission. Conclusion: Comprehensive preoperative evaluations, including pulmonary function and oxygenation assessment, are crucial for COVID-19 survivors undergoing elective surgery. Symptomatic patients showed lower pulse oximetry readings and higher respiratory and cardiovascular abnormalities rates. These findings emphasize the importance of optimizing perioperative management and minimizing complications by thoroughly assessing patients’ preoperative health status.